Religious Moderation as Lived Pedagogy: An Interpretive Case Study in Indonesian Secondary Schools - Sufiani Sufiani; Sumardona Sumardona (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
Research on religious moderation in education has grown substantially in recent years. However, existing studies have largely focused on conceptual debates, curriculum content, or outcome-based evaluations, while giving less empirical attention to how religious moderation is practiced in everyday school life. This study investigates how religious moderation is implemented in secondary schools in Kendari, the factors that shape its implementation, and its educational impacts on students and school culture. Using a qualitative case study within an interpretivist framework, the study collected data through semi-structured interviews with teachers and school stakeholders, as well as classroom and school activity observations. The data were analyzed thematically to identify recurring patterns of practice and meaning. The findings show that religious moderation is enacted through both intracurricular and extracurricular activities, such as integrating values of tolerance, mutual respect, and balanced religious understanding into classroom instruction, as well as through collective school programs, religious celebrations, and inter-student social activities. Its implementation is shaped by government policy support, shared school commitment, and teachers’ active role as mediators of inclusive values. The study also finds that these practices foster stronger social cohesion among students, improve communication across differences, encourage a balanced spiritual and social orientation, and create a more inclusive school climate. This study contributes to the field by offering an empirically grounded and integrated account of religious moderation as a lived pedagogical practice in Indonesian secondary education, particularly in a context that remains underrepresented in international scholarship.